2013
DOI: 10.1016/j.otsr.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of 447 SCORE® highly congruent mobile-bearing total knee arthroplasties after 5–10years follow-up

Abstract: Level IV continuous retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
2
15
1
Order By: Relevance
“…CAS has been developed in TKA to minimise outliers in component positioning and to improve final mechanical alignment and soft tissue balance [3, 4, 9, 10, 27, 31, 40]. Châtain et al [9] demonstrated that CAS enabled a more accurate soft tissue balance achievement and restoration of a neutral limb alignment with improved clinical scores when compared to the conventional mechanical technique.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CAS has been developed in TKA to minimise outliers in component positioning and to improve final mechanical alignment and soft tissue balance [3, 4, 9, 10, 27, 31, 40]. Châtain et al [9] demonstrated that CAS enabled a more accurate soft tissue balance achievement and restoration of a neutral limb alignment with improved clinical scores when compared to the conventional mechanical technique.…”
Section: Discussionmentioning
confidence: 99%
“…CAS has been developed in TKA to minimise outliers in component positioning and to improve final mechanical alignment and soft tissue balance [3, 4, 9, 10, 27, 31, 40]. Châtain et al [9] demonstrated that CAS enabled a more accurate soft tissue balance achievement and restoration of a neutral limb alignment with improved clinical scores when compared to the conventional mechanical technique. In addition, reporting the results issued from the Australian Orthopaedic Association National Joint Replacement Registry, de Steiger et al [35] emphasised that CAS reduced the overall rate of TKA revision as well as the rate of revision for loosening/lysis, particularly in patients less than 65 years of age in which higher rates of revision due to wear‐related issues were reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of tibial resection on valgus angulation under load was studied for tibial cuts made sequentially on each specimen at 6mm, 10mm, 14mm, 18mm and 24mm. Computer navigation (Amplitude® navigation system with a Polaris® infrared camera « Amplivision® » [3]) was used to position the tibial cutting guide at the selected depth, and to result in a cut with a posterior slope of 0° and a frontal tibial angulation at 90° to the tibial mechanical axis. Trackers for the navigation system were applied to the femoral and tibial diaphysis.…”
Section: Methodsmentioning
confidence: 99%